Low prevalence of archived integrase strand transfer inhibitors resistance associated mutations in Botswana before the roll out of dolutegravir based first line antiretroviral therapy - Maruapula, Dorcas; Ditshwanelo, Doreen; Pema, Marea N.; Bareng, Ontlametse T.; Choga, Wonderful T.; Moraka, Natasha O.; Mokgethi, Patrick T.; Seatla, Kaelo K.; Koofhethile, Catherine K.; Zuze, Boitumelo J.; Gaolathe, Tendani; Pretorius-Holme, Molly; et al. (Frontiers in Microbiology, 2024)
Background: We evaluated the prevalence of archived proviral drug resistance mutations (DRMs) associated with resistance to integrase strand transfer inhibitors (INSTIs) shortly before Botswana transitioned in 2016 to using dolutegravir (DTG)-based antiretroviral treatment in first-line regimens. Methods: We used the Stanford University HIV drug resistance database to analyze INSTIresistance associated mutations (RAMs) in a large representative population-based cohort of adults recruited in 30 geographically dispersed communities as part of the Botswana Combination Prevention Project (BCPP) cohort from 2013-2018. A total of 5144 HIV-1 proviral DNA sequences were included in our analysis; 1281 sequences were from antiretroviral therapy (ART)-naïve individuals and 3863 sequences were from non-nucleoside reverse transcriptase inhibitor (NNRTI) ART-experienced individuals. None of the sequences were from DTG-ART experienced participants. Results: The overall prevalence of major INSTIs DRMs was 1.11% (95% CI 0.82%-1.39%). The prevalence of INSTI DRMs in ART-naïve individuals was 1.64% (21/1281) and 0.93% (36/3863) in ART-experienced individuals. Major INSTI-RAMs detected in ART-naïve individuals were E138K(2/1281; 0.16%), G140R (8/1281;0.62%), E92G (2/1281;0.16%), R263K (5/1281; 0.4%), N155H (1/1281; 0.08%), P145S (1/1281;0.008%). Among the ART-experienced individuals, major INSTI RAMs detected were E138K (4/3863; 0.10%), G140R (25/3863;0.65%), G118R (2/3863, 0.05%), R263K (4/3863, 0.10%), T66I (1/3863;0.03%), E138K+G140R (1/3863, 0.03%|), G140R + R263K (1/3863, 0.03%). High-level resistance to cabotegravir (CAB), elvitegravir (EVG), and raltegravir (RAL) was detected in 0.70%, 0.16% and 0.06% of the individuals, respectively. Notably, bictegravir (BIC) and dolutegravir (DTG) showed no high-level resistance.The overall prevalence of archived INSTI RAMs in Botswana was low prior to transitioning to first-line DTG-based ART regimens, and did not differ between ART-naïve and ARTexperienced individuals. Ongoing surveillance of INSTI DRMs in Botswana will allow for reassessment of INSTI resistance risk following nationwide DTG rollout.